2016
DOI: 10.1007/s12928-016-0403-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stent platform on longitudinal stent deformation: an in vivo frequency domain optical coherence tomography study

Abstract: Recently, longitudinal coronary stent deformation has been highlighted as a possible cause of drug-eluting stent failure. Although bench tests and in vivo studies have demonstrated difference in longitudinal stent strength among the stents with different platforms, its clinical impact is still unknown. Furthermore, it is unknown if modified stent platform favorably affect the incidence of stent deformation. The aim of this study was to investigate the longitudinal deformation of the everolimus-eluting stents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Recent reports have identified risk factors for stent deformation, which included stent design; post‐balloon dilatation; complex lesions; ostial, bifurcation, and left main trunk lesions; extra support devices; guiding catheter; guidewires; and low stent inflation pressure . In addition to the procedural and morphological characteristics, stent types have been reported to be associated with stent deformation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent reports have identified risk factors for stent deformation, which included stent design; post‐balloon dilatation; complex lesions; ostial, bifurcation, and left main trunk lesions; extra support devices; guiding catheter; guidewires; and low stent inflation pressure . In addition to the procedural and morphological characteristics, stent types have been reported to be associated with stent deformation.…”
Section: Discussionmentioning
confidence: 99%
“…14 We hypothesized that, as the mechanism of this longitudinal stent elongation after post-balloon dilatation, although the force of postballoon dilatation typically exerted toward the radial axis of the catheter; guidewires; and low stent inflation pressure. [9][10][11] In addition to the procedural and morphological characteristics, stent types have been reported to be associated with stent deformation. A previous OCT study reported that, compared to cobalt-chromium everolimus-eluting stents, platinum-chromium everolimus-eluting stents showed a lower tendency for malapposed struts, 19 but in contrast, recent studies reported that the Promus Element® stent (platinum-chromium stent) often demonstrated deformation 8,9,20 The vast majority of stent design included in this study was second-and third-generation drug eluting stents ( Supplemental Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations